The prevalence of primary aldosteronism and evolving approaches for treatment. (October 2019) - Yozamp, Nicholas; Vaidya, Anand
Abstract: Over six decades since primary aldosteronism was first described, much has been learned about its prevalence and optimal treatment. Estimates of the prevalence of primary aldosteronism have increased considerably over the years, even exceeding 20% in some populations of resistant hypertension. Even in patients with normal blood pressures, the prevalence of overt primary aldosteronism and dysregulated aldosterone production may be more common than appreciated. Emerging data support the concept that primary aldosteronism may be better characterized as a continuum of renin-independent aldosterone production, whose severity influences the clinical presentation and risk of incident cardiovascular disease. Mineralocorticoid receptor antagonists and adrenalectomy are the mainstay treatments for primary aldosteronism and have long been considered equally efficacious. However, recent data suggest that although surgical adrenalectomy can effectively reduce cardiovascular risk, mineralocorticoid receptor antagonist therapy may require a physiologic approach to optimize efficacy.